Extraction of synonymies, hyponymies, overlappings and homonymies from XML schemas at various "severity" levels - De Meo, P.; Terracina, G.; Quattrone, G.; Ursino, D. (Proceedings. International Database Engineering and Applications Symposium, 2004. IDEAS '04, 2004)
This work presents an approach for the semiautomatic, uniform extraction of synonymies, hyponymies, overlappings and homonymies existing among concepts of different XML schemas. The proposed approach is specialized for XML, is almost automatic, semantic and "light". As a further, original, peculiarity, it is parametric w.r.t. a "severity level" against which the extraction task is performed.